Measuring internet audiences and usability of an online course - Zaphiris, Panayiotis; Zacharia, Giorgos (My University, 2001)
In this paper, we attempt to outline a variety of methods used to construct a richer conception of the audience of a modern Greek online course. First an analysis of the design methodology employed in this specific case study is provided and then examples of how valuable usability information can be extracted from the log files are presented. Conclusions, related to the analysis of the log files, about the usability of the course are also provided.
Keywords: Distance learning; Human; Human computer interaction; Online communities; Server logs analysis; Web usability